Preparation method of composite water purification filter material
Through the combination technology of activated carbon/quartz sand composite material and modified polymer gel, a large-effect water purification filter with high efficiency removal ability and wear resistance was prepared, solving the shortcomings of existing water purification filter materials in terms of microbial removal rate and maintenance costs.
Patent Information
- Application Number
- CN202411856326.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-14
AI Technical Summary
The existing water purification filters are not ideal in terms of microbial removal rates and are time-consuming and labor-intensive for regular maintenance.
The combined technology of activated carbon/quartz sand composite material and modified polymer gel is used to prepare composite water purification filter material through grinding, dropping, pressing and sintering to form a thin film structure with efficient removal capabilities.
It achieves efficient removal of suspended substances, colloids and organic matter from water, significantly reduces turbidity and chromaticity, excellent wear resistance and mechanical strength, extends service life and reduces maintenance costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water filtration, and in particular to a method for preparing a composite water purification filter material. Background Art
[0002] Water purification filter media refers to various materials used in water treatment to remove impurities and pollutants in water through physical, chemical or biological methods. The function of water purification filter media is to improve water quality so that it meets the corresponding standards or meets specific usage requirements. Water purification filter media are widely used in municipal water supply, industrial water treatment, household water purification equipment and other fields.
[0003] Water purification filter media is a key material in the water treatment process. It removes various pollutants in the water through physical, chemical or biological methods to improve water quality. The selection of appropriate water purification filter media requires consideration of the type of pollutants, water quality requirements and treatment process, and regular maintenance and management to ensure its long-term and stable treatment effect.
[0004] However, the regular on-site maintenance of existing water purification filter materials is time-consuming and labor-intensive, and the removal rate of microorganisms is not ideal. Summary of the invention
[0005] In order to solve the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a composite water purification filter material.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing a composite water purification filter material, comprising the following steps: S1. Weigh the following raw materials: S2. A preparation method of an activated carbon / quartz sand composite material comprises: calcining quartz sand at a high temperature to remove impurities, grinding the quartz sand and activated carbon into powder, adding a potassium hydroxide standard solution and a zinc chloride standard solution to the mixed powder, grinding and mixing the mixed powder evenly, placing the mixed powder in a mold for pressing and shaping, evaporating excess water at a certain temperature, placing the dried composite material in a high-temperature furnace for sintering, and after sintering, slowly cooling the composite material to obtain an activated carbon / quartz sand composite material; S3. Pour the activated carbon / quartz sand composite material into the modified polymer gel and mix them evenly. The modified polymer gel is added in an amount that covers the activated carbon / quartz sand composite material by 1-2 cm, so that a thin film is formed on the surface of the activated carbon / quartz sand composite material, and then dried and heat-treated to finally form a composite water purification material.
[0007] Preferably, in step S2, quartz sand is calcined at high temperature to remove impurities, and then ground into powder together with activated carbon and mixed. A standard solution of potassium hydroxide and a standard solution of zinc chloride are added to the mixed powder and mixed evenly. During the process of grinding and mixing, a small amount of nano-silicon oxide is added and mixed evenly. After mixing, the mixture is placed in a mold and pressed into shape.
[0008] Preferably, in step S2, after the mold is pressed and shaped, excess water is evaporated at 100-120°C.
[0009] Preferably, the preparation method of the modified polymer comprises: The polyvinyl alcohol is dissolved in 70-80°C water and stirred. Glutaraldehyde is added during the stirring process and the stirring is continued. After the stirring is completed, the mixture is allowed to stand and cool for 20-35 minutes. The glue solution is poured into a reactor and, under ultraviolet irradiation conditions, 35% of calcium carbonate by total weight, 75% of epoxy resin liquid by total weight and nano-silver are sequentially added into the reactor. While stirring, an inert gas is introduced. After stirring for 10-13 minutes, the temperature is raised to 80-100°C, ultrasonic treatment is added, and stirring is continued. After stirring for 35-55 minutes, the remaining 65% of calcium carbonate and 25% of epoxy resin liquid are added until the stirring is completed to obtain a modified polymer gel.
[0010] Preferably, in step S2, the mass ratio of activated carbon to quartz sand is 1:1, the amount of sodium hydroxide standard solution added is 2-6% of the total mass of activated carbon and quartz sand, and the amount of zinc chloride standard solution added is 1-4% of the total mass of activated carbon and quartz sand.
[0011] Preferably, in the preparation method of modified polyvinyl alcohol, the mass ratio of polyvinyl alcohol to glutaraldehyde is 4-5:0.5-1, the added amount of calcium carbonate is 10-20% of the total mass of polyvinyl alcohol and glutaraldehyde, the added amount of epoxy resin is 8-15% of the total mass of polyvinyl alcohol and glutaraldehyde, and the added amount of nanosilver is 8-15% of the total mass of polyvinyl alcohol and glutaraldehyde.
[0012] First, the activated carbon and quartz sand are ground into powder, and then potassium hydroxide standard solution and zinc chloride standard solution are added dropwise. During the adding process, a small amount of nano-silicon oxide is added. The potassium hydroxide standard solution and the zinc chloride standard solution first react with the activated carbon and quartz sand to change their pore structures, and then continue to react during the heating process. During the reaction process, adding a small amount of nano-silicon oxide can change the stability and energy performance of the quartz sand, and can also catalyze the reaction of the potassium hydroxide standard solution and the zinc chloride standard solution to make its pore structure more standard.
[0013] Polyvinyl alcohol has good water solubility and can form a tough, transparent film that can isolate harmful substances more effectively. It can be combined with calcium carbonate and epoxy resin to form a three-dimensional cross-linked network structure, which can enhance its mechanical strength and rigidity, increase the toughness of the film, and extend its use time to avoid film breakage under long-term water impact. Epoxy resin also has good adhesive properties and good heat resistance. The modified polymer gel can also effectively inhibit bacteria and effectively isolate microorganisms.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The removal rate of suspended solids of the present invention is as high as 96%, the removal rate is high, and the process is simple.
[0015] 2. The filter material of the present invention has been precisely screened and processed, and can efficiently remove suspended matter, colloids and organic matter in water, significantly reduce turbidity and chromaticity, and has excellent wear resistance and mechanical strength, ensuring long-term stable operation and reducing maintenance costs. It is a highly cost-effective water purification filter material choice, which not only has significant effects, but also has a long service life, saving the frequency and cost of replacing filter materials. DETAILED DESCRIPTION
[0016] The invention is described in detail below with reference to the embodiments. Example
[0017] A method for preparing a composite water purification filter material comprises the following steps: S1. Weigh the following raw materials: S2. The preparation method of the activated carbon / quartz sand composite material comprises: calcining quartz sand at high temperature to remove impurities, grinding and mixing the quartz sand with activated carbon into powder, dropping potassium hydroxide standard solution and zinc chloride standard solution into the mixed powder, adding a small amount of nano silicon oxide and mixing them evenly during the grinding and mixing process, placing the mixed powder in a mold for pressing and shaping, evaporating excess water at 100° C., placing the dried composite material in a high-temperature furnace for sintering, and after sintering, slowly cooling the composite material to obtain the activated carbon / quartz sand composite material, wherein the mass ratio of activated carbon to quartz sand is 1:1, the amount of sodium hydroxide standard solution added is 2% of the total mass of activated carbon and quartz sand, and the amount of zinc chloride standard solution added is 1% of the total mass of activated carbon and quartz sand; S3. Pour the activated carbon / quartz sand composite material into the modified polymer gel and mix them evenly. The modified polymer gel is added in an amount that covers the activated carbon / quartz sand composite material by 1 cm, so that a thin film is formed on the surface of the activated carbon / quartz sand composite material, and then dried and heat-treated to finally form a composite water purification material.
[0018] Polyvinyl alcohol was dissolved in 70° C. water and stirred. Glutaraldehyde was added during the stirring process and the stirring was continued. After the stirring was completed, the mixture was allowed to stand and cool for 20 minutes. The gel was poured into a reactor and 35% of calcium carbonate by weight, 75% of epoxy resin liquid by weight and nano-silver were added to the reactor in sequence under ultraviolet irradiation. Inert gas was introduced into the reactor while stirring. After stirring for 10 minutes, the temperature was raised to 80° C., ultrasonic treatment was added, and stirring was continued. After stirring for 35 minutes, the remaining 65% of calcium carbonate and 25% of epoxy resin liquid were added until the stirring was completed to obtain a modified polymer gel. The mass ratio of polyvinyl alcohol to glutaraldehyde was 4:0.5. The amount of calcium carbonate added was 10% of the total mass of polyvinyl alcohol and glutaraldehyde, the amount of epoxy resin added was 8% of the total mass of polyvinyl alcohol and glutaraldehyde, and the amount of nano-silver added was 8% of the total mass of polyvinyl alcohol and glutaraldehyde. Example
[0019] A method for preparing a composite water purification filter material comprises the following steps: S1. Weigh the following raw materials: S2. The preparation method of the activated carbon / quartz sand composite material comprises: calcining quartz sand at high temperature to remove impurities, grinding and mixing the quartz sand with activated carbon into powder, dropping potassium hydroxide standard solution and zinc chloride standard solution into the mixed powder, adding a small amount of nano silicon oxide and mixing them evenly during the grinding and mixing process, placing the mixed powder in a mold for pressing and shaping, evaporating excess water at 110° C., placing the dried composite material in a high-temperature furnace for sintering, and after sintering, slowly cooling the composite material to obtain the activated carbon / quartz sand composite material, wherein the mass ratio of activated carbon to quartz sand is 1:1, the amount of sodium hydroxide standard solution added is 3% of the total mass of activated carbon and quartz sand, and the amount of zinc chloride standard solution added is 2% of the total mass of activated carbon and quartz sand; S3. Pour the activated carbon / quartz sand composite material into the modified polymer gel and mix them evenly. The modified polymer gel is added in an amount that covers the activated carbon / quartz sand composite material by 2 cm, so that a thin film is formed on the surface of the activated carbon / quartz sand composite material, and then dried and heat-treated to finally form a composite water purification material.
[0020] Polyvinyl alcohol was dissolved in 75°C water and stirred. Glutaraldehyde was added during the stirring process and the stirring was continued. After the stirring was completed, the mixture was allowed to stand and cool for 20-35 minutes. The gel was poured into a reactor and calcium carbonate (35% by weight), epoxy resin liquid (75% by weight) and nano-silver (75% by weight) were added to the reactor in sequence under ultraviolet irradiation. Inert gas was introduced into the reactor while stirring. After stirring for 12 minutes, the temperature was raised to 85°C, ultrasonic treatment was added, and stirring was continued. After stirring for 40 minutes, the remaining 65% of calcium carbonate and 25% of epoxy resin liquid were added until the stirring was completed to obtain a modified polymer gel. The mass ratio of polyvinyl alcohol to glutaraldehyde was 45:-1. The amount of calcium carbonate added was 12% of the total mass of polyvinyl alcohol and glutaraldehyde. The amount of epoxy resin added was 8% of the total mass of polyvinyl alcohol and glutaraldehyde. The amount of nano-silver added was 9% of the total mass of polyvinyl alcohol and glutaraldehyde. Example
[0021] A method for preparing a composite water purification filter material comprises the following steps: S1. Weigh the following raw materials: S2. The preparation method of the activated carbon / quartz sand composite material comprises: calcining quartz sand at high temperature to remove impurities, grinding and mixing the quartz sand with activated carbon into powder, dropping potassium hydroxide standard solution and zinc chloride standard solution into the mixed powder, adding a small amount of nano silicon oxide and mixing them evenly during the grinding and mixing process, placing the mixed powder in a mold for pressing and shaping, evaporating excess water at 120° C., placing the dried composite material in a high-temperature furnace for sintering, and after sintering, slowly cooling the composite material to obtain the activated carbon / quartz sand composite material, wherein the mass ratio of activated carbon to quartz sand is 1:1, the amount of sodium hydroxide standard solution added is 6% of the total mass of activated carbon and quartz sand, and the amount of zinc chloride standard solution added is 4% of the total mass of activated carbon and quartz sand; S3. Pour the activated carbon / quartz sand composite material into the modified polymer gel and mix them evenly. The modified polymer gel is added in an amount that covers the activated carbon / quartz sand composite material by 2 cm, so that a thin film is formed on the surface of the activated carbon / quartz sand composite material, and then dried and heat-treated to finally form a composite water purification material.
[0022] Polyvinyl alcohol is dissolved in water at 80° C. and stirred. Glutaraldehyde is added during the stirring process and the stirring is continued. After the stirring is completed, the mixture is allowed to stand and cool for 35 minutes. The glue solution is poured into a reactor and, under ultraviolet irradiation conditions, 35% of calcium carbonate by total weight, 75% of epoxy resin liquid by total weight and nano-silver are sequentially added into the reactor while stirring. Inert gas is introduced. After stirring for 13 minutes, the temperature is raised to 100° C., ultrasonic treatment is added, and stirring is continued. After stirring for 55 minutes, the remaining 65% of calcium carbonate and 25% of epoxy resin liquid are added until the stirring is completed to obtain a modified polymer gel. The mass ratio of polyvinyl alcohol to glutaraldehyde is 5:1. The amount of calcium carbonate added is 20% of the total mass of polyvinyl alcohol and glutaraldehyde. The amount of epoxy resin added is 15% of the total mass of polyvinyl alcohol and glutaraldehyde. The amount of nano-silver added is 15% of the total mass of polyvinyl alcohol and glutaraldehyde.
[0023] Comparative Example 1 Compared with Example 2, Comparative Example 1 does not add silicon oxide, and the rest is the same as Example 2.
[0024] Comparative Example 2 Compared with Example 2, in Control Example 2, the activated carbon and quartz sand are directly ground into blocks and then potassium hydroxide and zinc chloride solutions are added dropwise to obtain an activated carbon / quartz sand composite material, and the rest is the same as in Example 2.
[0025] Comparative Example 3 Compared with Example 2, no modified polymer gel was added in Control Example 3, and the rest was the same as in Example 2.
[0026] The removal rates of the water purification filter materials prepared in Examples 1-3 and Comparative Examples 1-3 were obtained by experimental methods, and the specific data are shown in Table 1; Experimental methods Collect water samples: Collect samples from the water supply to be treated or directly from the water inlet of the water treatment equipment.
[0027] Preliminary treatment: The collected water samples shall be initially filtered or pretreated as needed.
[0028] Record initial conditions: Following standard operating procedures, determine and record the initial concentration of contaminants in the water sample.
[0029] The initial water sample was divided into 6 parts, and treated with the water purification filter materials prepared in Examples 1-3 and Comparative Examples 1-3 respectively.
[0030] Collect treated water samples.
[0031] Using the same analytical method, determine and record the concentration of contaminants in the treated water samples.
[0032] Table 1 It can be seen that Example 2 is the best solution, with the highest removal rates of suspended matter and microorganisms.
[0033] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the patent and protection scope of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a composite water purification filter material, characterized in that: The following steps are involved: S1. Weigh the following raw materials: S2. A preparation method of an activated carbon / quartz sand composite material comprises: calcining quartz sand at a high temperature to remove impurities, grinding the quartz sand and activated carbon into powder, adding a potassium hydroxide standard solution and a zinc chloride standard solution to the mixed powder, grinding and mixing the mixed powder evenly, placing the mixed powder in a mold for pressing and shaping, evaporating excess water at a certain temperature, placing the dried composite material in a high-temperature furnace for sintering, and after sintering, slowly cooling the composite material to obtain an activated carbon / quartz sand composite material; S3. Pour the activated carbon / quartz sand composite material into the modified polymer gel and mix them evenly. The modified polymer gel is added in an amount that covers the activated carbon / quartz sand composite material by 1-2 cm, so that a thin film is formed on the surface of the activated carbon / quartz sand composite material, and then dried and heat-treated to finally form a composite water purification material.
2. A method for preparing a composite water purification filter material as claimed in claim 1, wherein in step S2, quartz sand is calcined at high temperature to remove impurities, and then ground into powder together with activated carbon, and a standard potassium hydroxide solution and a standard zinc chloride solution are added dropwise into the mixed powder to grind and mix uniformly, and a small amount of nano-silicon oxide is added to mix uniformly, and after mixing, the mixture is placed in a mold for pressing and shaping.
3. The method for preparing a composite water purification filter material according to claim 2, characterized in that: In step S2, after the mold is pressed and shaped, excess water is evaporated at 100-120°C.
4. The method for preparing a composite water purification filter material according to claim 1, characterized in that: The method for preparing the modified polymer comprises: The polyvinyl alcohol is dissolved in 70-80°C water and stirred. Glutaraldehyde is added during the stirring process and the stirring is continued. After the stirring is completed, the mixture is allowed to stand and cool for 20-35 minutes. The glue solution is poured into a reactor and, under ultraviolet irradiation conditions, 35% of calcium carbonate by total weight, 75% of epoxy resin liquid by total weight and nano-silver are sequentially added into the reactor. While stirring, an inert gas is introduced. After stirring for 10-13 minutes, the temperature is raised to 80-100°C, ultrasonic treatment is added, and stirring is continued. After stirring for 35-55 minutes, the remaining 65% of calcium carbonate and 25% of epoxy resin liquid are added until the stirring is completed to obtain a modified polymer gel.
5. The method for preparing a composite water purification filter material according to claim 1, characterized in that: In step S2, the mass ratio of activated carbon to quartz sand is 1:1, the amount of sodium hydroxide standard solution added is 2-6% of the total mass of activated carbon and quartz sand, the amount of zinc chloride standard solution added is 1-4% of the total mass of activated carbon and quartz sand, and the amount of nano-silicon oxide added is 0.8-2% of the total mass of activated carbon and quartz sand.
6. The method for preparing a composite water purification filter material according to claim 4, characterized in that: In the preparation method of modified polyvinyl alcohol, the mass ratio of polyvinyl alcohol to glutaraldehyde is 4-5:0.5-1, the added amount of calcium carbonate is 10-20% of the total mass of polyvinyl alcohol and glutaraldehyde, the added amount of epoxy resin is 8-15% of the total mass of polyvinyl alcohol and glutaraldehyde, and the added amount of nanosilver is 8-15% of the total mass of polyvinyl alcohol and glutaraldehyde.